2012
DOI: 10.5194/cp-8-1897-2012
|View full text |Cite
|
Sign up to set email alerts
|

Depositional dynamics in the El'gygytgyn Crater margin: implications for the 3.6 Ma old sediment archive

Abstract: Abstract. The combination of permafrost history and dynamics, lake level changes and the tectonical framework is considered to play a crucial role for sediment delivery to El'gygytgyn Crater Lake, NE Russian Arctic. The purpose of this study is to propose a depositional framework based on analyses of the core strata from the lake margin and historical reconstructions from various studies at the site. A sedimentological program has been conducted using frozen core samples from the 141.5 m long El'gygytgyn 5011-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 45 publications
1
53
0
Order By: Relevance
“…The remaining sample parts were freeze-dried and then the absolute ice content was determined and is expressed as total water content equivalent in weight percentage (wt%) of the moist sample. The solid portion of the sample underwent a standard suite of sediment analyses, which is described elsewhere (Schwamborn et al, 2012a). Precipitation (snow and rain) and surface water from the lake and tundra ponds were sampled between early May and late August 2003.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining sample parts were freeze-dried and then the absolute ice content was determined and is expressed as total water content equivalent in weight percentage (wt%) of the moist sample. The solid portion of the sample underwent a standard suite of sediment analyses, which is described elsewhere (Schwamborn et al, 2012a). Precipitation (snow and rain) and surface water from the lake and tundra ponds were sampled between early May and late August 2003.…”
Section: Methodsmentioning
confidence: 99%
“…2). The sediment interpretation of core 5011-3 concluded that the strata belong to different portions of a prograding fan delta that enters Lake El'gygytgyn from the west (Schwamborn et al, 2012a). Between 141.0 and 117.0 m core depth several thin (< 5 cm thick) sand layers intercalate with sandy gravel and are interpreted to be the bottomset facies of prodelta sediments, which were deposited in deeper water.…”
Section: Sediment Strata and Ground-ice Occurrencementioning
confidence: 99%
See 3 more Smart Citations